Phosphorylation of Rad55 on Serines 2, 8, and 14 Is Required for Efficient Homologous Recombination in the Recovery of Stalled Replication Forks - Herzberg, Kristina (American Society for Microbiology, 2006)
DNA damage checkpoints coordinate the cellular response to genotoxic stress and arrest the cell cycle in response to DNA damage and replication fork stalling. Homologous recombination is a ubiquitous pathway for the repair of DNA double-stranded breaks and other checkpoint-inducing lesions. Moreover, homologous recombination is involved in postreplicative tolerance of DNA damage and the recovery of DNA replication after replication fork stalling. Here, we show that the phosphorylation on serines 2, 8, and 14 (S2,8,14) of the Rad55 protein is specifically required for survival as well as for normal growth under genome-wide genotoxic stress. Rad55 is a Rad51 paralog in Saccharomyces cerevisiae and functions in the assembly of the Rad51 filament, a central intermediate in recombinational DNA repair. Phosphorylation-defective rad55-S2,8,14A mutants display a very slow traversal of S phase under DNA-damaging conditions, which is likely due to the slower recovery of stalled replication forks or the slower repair of replication-associated DNA damage. These results suggest that Rad55-S2,8,14 phosphorylation activates recombinational repair, allowing for faster recovery after genotoxic stress.